Indacenodithiophene–benzothiadiazole organic field-effect transistors with gravure-printed semiconductor and dielectric on plastic. (8th October 2015) - Higgins, Stuart G.; Muir, Beinn V.O.; Heeney, Martin; Campbell, Alasdair J.
Abstract: Abstract : We demonstrate the gravure printing of a high-performance indacenodithiophene (IDT) copolymer, indacenodithiophene–benzothiadiazole (C16 IDT–BT), onto self-aligned organic field-effect transistor architectures on flexible plastic substrates. We observed that the combination of a gravure-printed dielectric with gravure-printed semiconductor yielded devices with higher mean-effective mobility than devices manufactured using photolithographically patterned dielectric. Peak mobilities of μ = 0.1 cm 2 V −1 s −1 were measured, and exceed previous reports for non-printed C16 IDT-BT on non-flexible silicon substrates.